Hadith Ahkam Analysis About Working at Night and Its Implications for the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia Number: Kep.233 /Men/2003 - Abdul wakhid; Imron Rosyadi; Isman (al-Afkar, Journal For Islamic Studies, 2024)
Humans need work to meet financial needs and meet religious demands. Nighttime work is becoming increasingly common for various reasons such as job requirements, time flexibility and economic demands. However, in religious teachings, there are provisions related to working at night that need to be understood. This research aims to analyze the legal provisions for working at night according to the hadith of the Prophet Muhammad SAW and their implications for the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia No. 233/Men/2003. The research method used is a qualitative approach using narrative or descriptive qualitative study methods. The research results show that the law on working at night according to the hadith is permissible or permissible as long as it meets several conditions, such as being able to perform the morning prayer on time, even praying at night and maintaining religious principles. Implications for ministerial decisions include the need to guarantee worship time, adequate rest time and health insurance for workers who work at night.